Personal role-play position of a modern student -psychologist (Actual Problems of Psychology in Educational Institutions, 2022)
In the article we are talking about the personal role-play positions of a modern student-psychologist. The basic theoretical positions are determined and features of roles in society are characterized. A study was carried out to identify the actual roles and compared the importance of the personal and professional sphere of a modern student-psychologist.
Keywords: social role; role-play theory of personality; role-based psychotherapy; role-play expectations; role-based behavior